Skill-bias and wage inequality in the EU New Member States: Empirical investigation - Jan Pintera (Charles University in Prague, Institute of Economic Studies (IES), 2022)
We use the individual-level data on income and education level from the EU-SILC database to investigate the trends in income distribution and wage polarization in the EU New Member States. We do not confirm the existence of job polarization in wages and employment that has been observed in the United States or other developed countries. Rather, we document decreasing inequality, particularly in Czechia, Poland, Hungary and Slovakia. Also, our estimates of the elasticity of substitution between low and high skill labour are higher than often found in other countries. These results imply a different impact of globalization on the labour markets in the EU New Member States than in other countries. However, it remains unclear whether these differences are temporary or will prevail in the future.
Keywords: J30; J31; O14; O31; O33; 330; Labor Markets; Technological Change; Polarization; Skills